HMGA1 amplifies Wnt signalling and expands the intestinal stem cell compartment and Paneth cell niche - Lingling Xian (Nature Portfolio, 2017)
The function of high mobility group A1 (Hmga1) chromatin remodelling proteins in intestinal stem cells (ISC) is unknown. Here, the authors show that Hmga1 amplifies Wnt/β-catenin signalling to enhance self-renewal and inducesSox9to expand the Paneth cell compartment and enrich the ISC niche.